Synthesis of polyhydroxylated azetidine iminosugars and 3-hydroxy-N-methylazetidine-2-carboxylic acid from d-glucose. Issue 31 (5th August 2015) - Lawande, Pravin P.; Sontakke, Vyankat A.; Nair, Roopa J.; Khan, Ayesha; Sabharwal, Sushma G.; Shinde, Vaishali S.
Abstract: The azetidine iminosugars, (2 S, 3 R )-2-(( R )-1, 2-dihydroxyethyl)azetidin-3-ol3, (2 R, 3 R )-2-(hydroxymethyl)azetidin-3-ol4, and (2 S, 3 R )-3-hydroxy- N -methylazetidine-2-carboxylic acid5 were synthesized fromd -glucose derived 3- N -benzyloxycarbonyl-3-deoxy-1, 2- O -isopropylidene-α-d -xylofuranose8 using intramolecular Mitsunobu reaction as a key step. The glycosidase inhibitory activity of compounds3 –5 was screened against various enzymes. Amongst all synthesized compounds, the N -methylated compound5 exhibited significant inhibitory activity against amyloglucosidase from Aspergillus niger in micro molar range. Graphical abstract: